Permissive Attitudes to Domestic Violence on Women in Indonesia - Oktriyanto, Oktriyanto; Nugraha, Arga; Puspitasari, Mardiana Dwi; Nasution, Sri Lilestina; Novianafari, Ifa Prasetya (IAIN Pekalongan, 2021)
Violence against women occurs in almost all countries and has become a global issue that is often reviewed and discussed at various seminars. The United Nations defines violence against women as